Fabrication of micro and nanostructures on glass using non-isothermal thermal imprinting - Raja Murfiqah, Raja Mohd Fouzy; Norfazilasari, Yasman; Mohd Zairulnizam, Mohd Zawawi (Elsevier Ltd, 2024)
The formation of micro/nano scale pattern features on glass using direct thermal imprinting has gained continuous attention due to its potential to replicate glass with various functional surfaces at an atomic scale resolution. Unfortunately, the long thermal cycle issue in regular thermal imprinting remains the main obstacle that hampered the process to be viable for mass production. In this paper, the fabrication of micro/nano scale pattern features directly on glass substrate using non-isothermal thermal imprinting is proposed. Compared to conventional thermal imprinting, this method eliminates the serial process of heating, soaking, pressing, demolding, and cooling that commonly took place in one close chamber. Therefore, the duration of each imprinting cycle is significantly decreased, which in turn could reduce the cost per unit price to fabricate these glass devices with micro and nanostructures. The morphology of these imprinted glass nanograting and microlens array (MLA) was characterized via the scanning electron microscope (SEM), atomic force microscope (AFM) and surface profiler. Overall, the imprinted nanograting and MLA pattern using the non-isothermal thermal imprinting method result showed good replication fidelity, comparable to the regular thermal imprinting and outperforms the conventional one in terms of overall cycle time reduction, minimized variation of mold temperature and lower energy consumption. The proposed method is expected to become an interesting approach for fabrication of various patterns directly on glass substrate with high pattern quality and shorter thermal cycle.